ANALISA YURIDIS SURROGATE MOTHER DARI ASPEK SAHNYA PERJANJIAN - Tomson Situmeang (to-ra, 2017)
Humans are created in pairs for future descendants (grandchildren), but not all pairs of humans can have children/ offspring with various causes. It turns out to be overcome by In Vitro Fertilization, one of which is Surrogate Mother, which is a woman who is willing on the basis of an agreement to lease her uterus to contain the seeds of the spouses, give birth and give birth to a couple by receiving certain rewards. But it is hindered by the provisions of existing laws and applicable in Indonesia as well as contrary to decency. Kata Kunci: Sahnya Perjanjian, Surrogate Mother, Ibu Pengganti, Sewa Rahim